A Primer for Oncoimmunology (Immunooncology). (July 2017) - Bolon, Brad; Aeffner, Famke
Oncoimmunology (or immunooncology) is a burgeoning specialty of precision ("personalized") medicine designed to heighten the antitumor response of the immune system against molecules expressed excessively or only by tumor cells. This focus is necessary, as cancers are polyclonal tissues comprised of antigenically heterogeneous cells, the exact composition of which is shaped by the balance between antitumor immunity and tumor-promoting inflammation. Key targets include enhancing immune system (especially T cell) reactivity, inhibiting immune checkpoints, and promoting tumor cytolysis. Therapeutic modalities to address these targets include administering antibodies, cytokines, or small molecules that directly stimulate the immune system, attack tumor-associated antigens, or interfere with tumor–stroma interactions; adoptive transfer of autologous T cells following ex vivo selection/expansion/activation (typically after lymphoid-depleting regimens and in conjunction with immunostimulatory therapy); and vaccination (against tumor antigens). Pathology involvement in oncoimmunology product development is critical to assess expression of target molecules in tumor cells, stromal cells, and tumor-infiltrating leukocytes.